Territorial Cohesion: Old (French) Wine in New Bottles? - Faludi, Andreas (Urban studies (Edinburgh, Scotland), 2004)
If finally accepted, the new concept of territorial cohesion could mean a formal planning role for the European Union. The paper traces the French roots of this concept. As other concepts in European integration, it is subject to multiple interpretations. The initial focus has been on regional economic development as such. At present, territorial cohesion is also held to mean (for example, in the White Paper on European Governance) the co-ordination of policies with an impact on one and the same territory. Originally adhering to a more interventionist approach to spatial planning, the French have learned to factor balanced and sustainable development, concerns of the so-called comprehensive integrated approach, into the equation. Germans, in turn, are seeing sense in the new French focus on 'services of general economic interest'. Experts from both countries agree on the need for a spatial framework for Community policies. Such a framework would look somewhat like the European Spatial Development Perspective, but as part of territorial cohesion policy as a shared responsibility of the Union and its member-states. This would vindicate ideas of the French pioneers of European spatial planning.